Transcutaneous Electrical Nerve Stimulation Reduces Movement‐Evoked Pain and Fatigue: A Randomized, Controlled Trial. Issue 5 (18th March 2020) - Dailey, Dana L.; Vance, Carol G. T.; Rakel, Barbara A.; Zimmerman, M. Bridget; Embree, Jennie; Merriwether, Ericka N.; Geasland, Katharine M.; Chimenti, Ruth; Williams, Jon M.; Golchha, Meenakshi; Crofford, Leslie J.; Sluka, Kathleen A.
Abstract : Objective: Fibromyalgia (FM) is characterized by pain and fatigue, particularly during physical activity. Transcutaneous electrical nerve stimulation (TENS) activates endogenous pain inhibitory mechanisms. This study was undertaken to investigate if using TENS during activity would improve movement‐evoked pain and other patient‐reported outcomes in women with FM. Methods: Participants were randomly assigned to receive active TENS (n = 103), placebo TENS (n = 99), or no TENS (n = 99) and instructed to use it at home during activity 2 hours each day for 4 weeks. TENS was applied to the lumbar and cervicothoracic regions using a modulated frequency (2–125 Hz) at the highest tolerable intensity. Participants rated movement‐evoked pain (primary outcome measure) and fatigue on an 11‐point scale before and during application of TENS. The primary outcome measure and secondary patient‐reported outcomes were assessed at baseline (time of randomization) and at 4 weeks. Results: After 4 weeks, a greater reduction in movement‐evoked pain was reported in the active TENS group versus the placebo TENS group (group mean difference –1.0 [95% confidence interval –1.8, –0.2]; P = 0.008) and versus the no TENS group (group mean difference –1.8 [95% confidence interval –2.6, –1.0]; P < 0.0001). A reduction in movement‐evoked fatigue was also reported in the active TENS group versus the placebo TENS group (group mean difference –1.4 [95% confidence interval –2.4, –0.4]; P = 0.001) and versus the no TENS group (group mean difference –1.9 [95% confidence interval –2.9, –0.9]; P = <0.0001). A greater percentage of the patients in the active TENS group reported improvement on the global impression of change compared to the placebo TENS group (70% versus 31%; P < 0.0001) and the no TENS group (9%; P < 0.0001). There were no TENS‐related serious adverse events, and <5% of participants experienced minor adverse events from TENS. Conclusion: Among women who had FM and were on a stable medication regimen, 4 weeks of active TENS use compared to placebo TENS or no TENS resulted in a significant improvement in movement‐evoked pain and other clinical outcomes. Further research is needed to examine effectiveness in a real‐world setting to establish the clinical importance of these findings.